The role of blocking circulation and emerging open water feedbacks on Greenland cold-season air temperature variability over the last century - Ballinger, Thomas J.; Hanna, Edward; Hall, Richard J.; Carr, J. Rachel; Brasher, Saber; Osterberg, Erich C.; Cappelen, John; Tedesco, Marco; Ding, Qinghua; Mernild, Sebastian H. (My University, 2021)
Substantial marine, terrestrial, and atmospheric changes have occurred over the Greenland region during the last century. Several studies have documented record-levels of Greenland Ice Sheet (GrIS) summer melt extent during the 2000s and 2010s, but relatively little work has been carried out to assess regional climatic changes in other seasons. Here, we focus on the less studied cold-season (i.e., autumn and winter) climate, tracing the long-term (1873-2013) variability of Greenland's air temperatures through analyses of coastal observations and model-derived outlet glacier series and their linkages with North Atlantic sea ice, sea surface temperature (SST), and atmospheric circulation indices. Through a statistical framework, large amounts of west and south Greenland temperature variance (up to r(2) similar to 50%) can be explained by the seasonally-contemporaneous combination of the Greenland Blocking Index (GBI) and the North Atlantic Oscillation (NAO; hereafter the combination of GBI and NAO is termed GBI). Lagged and concomitant regional sea-ice concentration (SIC) and the Atlantic Multidecadal Oscillation (AMO) seasonal indices account for small amounts of residual air temperature variance (r(2) < similar to 10%) relative to the GBI. The correlations between GBI and cold-season temperatures are predominantly positive and statistically-significant through time, while regional SIC conditions emerge as a significant covariate from the mid-20th century through the conclusion of the study period. The inclusion of the cold-season Pacific Decadal Oscillation (PDO) in multivariate analyses bolsters the air temperature variance explained by the North Atlantic regional predictors, suggesting the remote, background climate state is important to long-term Greenland temperature variability. These findings imply that large-scale tropospheric circulation has a strong control on surface temperature over Greenland through dynamic and thermodynamic impacts and stress the importance of understanding the evolving two-way linkages between the North Atlantic marine and atmospheric environment in order to more accurately predict Greenland seasonal climate variability and change through the 21st century.
Keywords: air temperatures; greenland; greenland blocking index; sea ice